Efficacy and Tolerability of Low-Dose Perampanel in Patients with Childhood-Onset Intractable Epilepsy - Hyeonmin Park; Hyunji Ahn; Han Na Jang; Hyun-Jin Kim; Mi-Sun Yum; Tae-Sung Ko (Korean Child Neurology Society, 2019)
Purpose The aim of this study was to evaluate the efficacy and tolerability of perampanel as adjunctive therapy in childhood-onset refractory epilepsy. Methods We retrospectively reviewed the medical records of 110 patients who were treated with perampanel in Asan Medical Center children's hospital. Two patients with poor compliance were excluded and 108 patients were enrolled. The clinical characteristics were reviewed, and the total seizure frequency before and after the add-on of perampanel was analyzed. Results The mean age of the patients (64 males) was 20.2 years (range, 10.5 to 35.6). The mean maintenance dose was 4.8 mg/day (2 to 10 mg). Eight patients (7.4%) achieved seizure freedom and 35 (32.4%) achieved a seizure reduction of ≥50%. Among them, three patients achieved seizure freedom with only 2 mg/day of perampanel. There was no significant difference in sex, age at seizure onset, duration of epilepsy, use of concomitant enzyme-inducing antiepileptic drugs, number of concomitant antiepileptic drugs, and adverse events between responders and non-responders. The retention rate was up to 68.0% in the first year and 59.5% in the second year of the study. Thirty-four patients (31.5%) reported adverse events: violence, somnolence, dizziness, drooling, weight gain, insomnia, and vomiting. There was no contributing factor for the adverse events, including sex, age, and the number of concomitant antiepileptic drugs and enzyme-inducing antiepileptic drugs when comparing the adverse event present group with the adverse event absent group. Conclusion Low-dose perampanel showed reasonable efficacy and tolerability in patients with refractory childhood-onset epilepsy. Further validation with pharmacokinetic studies is needed.